Magnitude and Correlates of Nicotine Dependence Among Brick Kiln Workers in A Rural Block of Murshidabad District, West Bengal, India - Prithwish Bandyopadhyay; Ritu Ghosh; Avijit Roy; Monojit Das (Medsci Publications, 2024)
Background: Nicotine dependence, a major public health problem, causes respiratory illnesses like asthma, COPD, chronic bronchitis, pneumoconiosis (e.g. silicosis) and respiratory infections. Occupational exposure of smoke and dust among brick kiln workers, in addition to tobacco addiction result in worsening of lung function and increase the risk of mortality. This study planned to estimate the prevalence of nicotine dependence among tobacco users of a brick kiln factory and identify the factors associated with nicotine dependence among them. Methodology: A cross-sectional study was conducted for a period of one month in a brick kiln of Murshidabad district among 135 adult workers who had been consuming any form of tobacco. Nicotine dependence was assessed by interviewing the participants using Fagerstrom Test for Nicotine Dependence (FTND) and Fagerstrom Nicotine Dependence Scale for smokeless Tobacco (FTND-ST) questionnaire. Results: About, 52.6% were smokers, 24.4% were smokeless tobacco users and 23% were addicted to both. Approximately 73.6% and 78.2% were nicotine dependent among smokers and smokeless tobacco users respectively. Age, illiteracy, initiation of nicotine consumption at an adult age and long duration of consumption were found to be significantly associated with nicotine dependence. Conclusions: A high level of nicotine dependence was found among workers. Awareness generation and behavior change communication is recommended.